2022
DOI: 10.3390/cancers14194938
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Postoperative Radiotherapy for Thymoma and Thymic Carcinoma: A Propensity-Matched Study Based on SEER Database

Abstract: (1) Objectives: The effect of postoperative radiotherapy (PORT) for thymoma and thymic carcinoma remains controversial. This study aimed to investigate the prognostic value of PORT for thymoma and thymic carcinoma in a population-based registry. (2) Methods: This retrospective study used the Surveillance, Epidemiology, and End Results (SEER) database to identify patients diagnosed with thymoma and thymic carcinoma between 2010 and 2019. Propensity score matching was performed to adjust statistical influences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The propensity score matching analysis with data from SEER database showed that PORT improved the OS and cancer‐specific survival of patients with Masaoka‐Koga stage IIB–IV TM, but had no significant survival benefit for patients with stage I–IIA TM. This study also proved the prognostic benefit of PORT in stage IIB TC for the first time 25 …”
Section: Radiotherapysupporting
confidence: 67%
See 1 more Smart Citation
“…The propensity score matching analysis with data from SEER database showed that PORT improved the OS and cancer‐specific survival of patients with Masaoka‐Koga stage IIB–IV TM, but had no significant survival benefit for patients with stage I–IIA TM. This study also proved the prognostic benefit of PORT in stage IIB TC for the first time 25 …”
Section: Radiotherapysupporting
confidence: 67%
“…This study also proved the prognostic benefit of PORT in stage IIB TC for the first time. 25 A prospective study conducted in 22 patients with locally advanced TET (stage III/IV) evaluated the efficacy of neoadjuvant CRT. Most (77%) patients can achieve R0 resection after neoadjuvant CRT.…”
Section: Who Classification Structural Variation Gene Mutationmentioning
confidence: 99%
“…Other studies have yielded different results, and the reason may be that the data processing was different— i.e. , putting stages III and IV into one group ( 29 31 ). The role of postoperative radiotherapy is controversial in patients with advanced thymic tumors, but some reports have recommended it ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, postoperative radiotherapy had no significant effect on diseasespecific survival but had a positive effect on overall survival time in patients with stage IV disease (15). Other studies have yielded different results, and the reason may be that the data processing was different-i.e., putting stages III and IV into one group (29)(30)(31). The role of postoperative radiotherapy is controversial in patients with advanced thymic tumors, but some reports have recommended it (32-34).…”
Section: B Amentioning
confidence: 99%
“…In addition, some population-based studies found no significant difference in OS or freedom from recurrence in stage II patients who received adjuvant radiation after surgery [35,36]. In summary, although PORT is controversial in patients with R0 resection, it is highly recommended for patients with thymomas who underwent incomplete resection, especially for patients with advanced thymomas [37][38][39]. In our study, although there was no significant difference between elderly thymoma patients who received PORT and those who did not, the risk of OS in patients who received PORT tended to decrease (HR = 0.83, p = 0.445).…”
Section: Discussionmentioning
confidence: 99%